PERSEPSI MAHASISWA UNIVERSITAS RIAU TENTANG POLITIK DI INDONESIA - Handayani, Endah Sri; Erlinda, Sri; Gimin, Gimin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to determine how the perception of students of the University of Riau about Politics in Indonesia. Based on the results of observations and surveys conducted by the author, there are still many students who are apathetic and do not understand politics in Indonesia. The research method used is descriptive analysis with a quantitative approach as a support. Data collection is done by observation, interviews, literature study and questionnaires. The sample in this study amounted to 150 respondents and was determined based on the Quota Sampling technique. While the process of distributing the questionnaire was carried out using the Incidental Sampling technique. The research instrument consists of 5 indicators, namely the State, Power, Decision Making, Public Policy, and Distribution. This means that they have a very high understanding of politics in Indonesia.Key Words: Students, Perceptions, Indonesian Politics